2005
DOI: 10.1021/jp054881d
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Vibrational Spectra of Mononitrated Benzo[a]pyrenes

Abstract: The molecules benzo[a]pyrene (BaP) and 1-, 3-, and 6-nitrobenzo[a]pyrene (1-NBaP, 3-NBaP, 6-NBaP) are currently of significant interest due to their presence in respirable combustion exhaust particulates and their mutagenic and carcinogenic properties. Structure-function correlations as well as spectroscopic signatures for trace analysis are necessary for these benzo[a]pyrene derivatives. In this paper, detailed infrared and Raman spectroscopic data of BaP and its three mononitrated isomers are provided for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
28
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 46 publications
8
28
0
Order By: Relevance
“…However, we note that distortion from planarity of the rings is almost insignificant (within 3°). The C-N and N-O bond lengths of the nitro group here computed at 1.47 and 1.23 Å are in agreement with the corresponding data for nitronaphthalenes [16], nitroanthracene [16], nitrophenanthrene [16], nitropyrenes [16], nitrobenzo[a]pyrenes [18], and dinitrobenzo[a]pyrenes [17] calculated at the same level. For 2, the N-O bond length for the azabenzene nitrogen atom is calculated to be 1.28 Å , which is 0.05 Å longer than the N-O bond lengths for the NO 2 group.…”
Section: Geometries and Nucleus Independent Chemical Shiftssupporting
confidence: 87%
See 1 more Smart Citation
“…However, we note that distortion from planarity of the rings is almost insignificant (within 3°). The C-N and N-O bond lengths of the nitro group here computed at 1.47 and 1.23 Å are in agreement with the corresponding data for nitronaphthalenes [16], nitroanthracene [16], nitrophenanthrene [16], nitropyrenes [16], nitrobenzo[a]pyrenes [18], and dinitrobenzo[a]pyrenes [17] calculated at the same level. For 2, the N-O bond length for the azabenzene nitrogen atom is calculated to be 1.28 Å , which is 0.05 Å longer than the N-O bond lengths for the NO 2 group.…”
Section: Geometries and Nucleus Independent Chemical Shiftssupporting
confidence: 87%
“…In this work we adopted the scaling factor reported by Irikura et al [24] for the B3LYP/6-31G* level (0.9594), derived by a leastsquares fitting procedure of experimental and calculated harmonic wavenumber values for a series of 41 common organic compounds. The use of scaling techniques generally reduces the deviation between experimental and calculated data, as demonstrated by the satisfactory results for some PAH derivatives [17,18,[25][26][27][28][29][30][31]. The simulated vibrational spectra were represented by convoluting the calculated wavenumber values with pure Lorentzian band shapes using a full-width at half-maximum of 10 cm -1 , as usually adopted in the literature [32][33][34][35].…”
Section: Ir and Raman Spectramentioning
confidence: 99%
“…However, owing to their high sensitivity to UV radiations, detection in the environment of DNBaPs is a hard task [21]. Hitherto, experimental and theoretical structural data of DNBaPs are not available, while X-ray structure of 6-NBaP [22] and Density Functional Theory (DFT) [23] geometries of 1-, 3-and 6-NBaP isomers [24] have been recently obtained. It is well established that nearly planar 1-NBaP and 3-NBaP are more mutagenic than the quasi-orthogonal 6-NBaP isomer [15][16][17][18]20].…”
Section: Introductionmentioning
confidence: 99%
“…For emissivity spectra, PAHs solid standards were used as received and placed in 50 mm diameter dishes. In both cases, PM 1 samples were analysed directly without any preparation, and the molecular vibrations of the two classes of spectra were identified using sources in the literature (Semmler et al, 1991;Carrasco Flores et al, 2005;Onchoke et al, 2006;Onchoke and Parks 2011).…”
Section: Preparation and Analysis Of The Pahs Solid Standardsmentioning
confidence: 99%
“…The signature molecular vibrations from the spectra were identified by comparison with the spectral database (Semmler et al, 1991;Allen et al, 1994;Carrasco Flores et al, 2005;Reff et al, 2005;Onchoke et al, 2006; The molecular vibrations of transmittance spectra were identified from the literature (Semmler et al, 1991;Carrasco Flores et al, 2005;Onchoke et al, 2006;Onchoke and Parks, 2011).…”
Section: Preparation and Analysis Of The Pahs Solid Standardsmentioning
confidence: 99%